Using the Jurkat reporter T cell line for evaluating the functionality of novel chimeric antigen receptors - Jahan, Farhana; Koski, Jan; Schenkwein, Diana; Ylä-Herttuala, Seppo; Göös, Helka; Huuskonen, Sini; Varjosalo, Markku; Maliniemi, Pilvi; Leitner, Judith; Steinberger, Peter; Bühring, Hans-Jörg; Vettenranta, Kim; et al. (Frontiers in Molecular Medicine, 2023)
Background: T cells that are genetically modified with chimeric antigen receptor (CAR) hold promise for immunotherapy of cancer. Currently, there are intense efforts to improve the safety and efficacy of CAR T cell therapies against liquid and solid tumors. Earlier we designed a novel CAR backbone (FiCAR) where the spacer is derived from immunoglobulin (Ig) -like domains of the signal-regulatory protein alpha (SIRPα). However, the analysis of novel CAR using primary T cells is slow and laborious. Methods: To explore the versatility of the CAR backbone, we designed a set of variant FiCARs with different spacer lengths and targeting antigens. To expedite the analysis of the novel CARs, we transduced the FiCAR genes using lentiviruses into Jurkat reporter T cells carrying fluorescent reporter genes. The expression of fluorescent markers in response to FiCAR engagement with targets was analyzed by flow cytometry, and cytotoxicity was evaluated using killing assays. Furthermore, the killing mechanisms that are employed by FiCAR-equipped Jurkat T cells were investigated by flow cytometry, and the intracellular pathways involved in signaling by FiCAR were analyzed by phosphoproteomic analysis using mass spectrometry. Results: Seven different CARs were designed and transduced into Jurkat reporter cells. We show that the SIRPα derived FiCARs can be detected by flow cytometry using the SE12B6A4 antibody recognizing SIRPα. Furthermore, FiCAR engagement leads to robust activation of NFκβ and NFAT signaling, as demonstrated by the expression of the fluorescent reporter genes. Interestingly, the Jurkat reporter system also revealed tonic signaling by a HER-2 targeting FiCAR. FiCAR-equipped Jurkat T cells were cytotoxic in cocultures with target cells and target cell engagement lead to an upregulation of CD107a on the Jurkat reporter T cell surface. Phosphoproteomic analyses confirmed signal transduction via the intracellular CD28/CD3ζ sequences upon the interaction of the FiCAR1 with its antigen. In addition, downstream signaling of CD3ζ/ZAP70- SLP-76-PLCγ, PI3K–AKT–NFκB pathways and activation of NFAT and AP-1 were observed. Conclusion: We conclude that the FiCAR backbone can be shortened and lengthened at will by engineering it with one to three SIRPα derived Ig-like domains, and the FiCARs are functional when equipped with different single chain variable fragment target binding domains. The Jurkat reporter system expedites the analysis of novel CARs as to their expression, signaling function, evaluation of tonic signaling issues and cytotoxic activity.